A study on the impact of UiTM's student toward business sector in Bandar Tun Razak Jengka Pahang / Ain Azwani Mohamad Yasin and Rabi' Atul 'Adawiyah Abdullah - Mohamad Yasin, Ain Azwani; Abdullah, Rabi' Atul 'Adawiyah (2013)
This study mainly analyzes the impact of UiTM Pahang students towards business sector in Bandar Tun Razak, Jengka. . Beside that, the objective was to identify the type of business and amount of spending by resident and non-resident degree student at UiTM Pahang based on the demographic information. Then, the researcher also wants to identify the level of UiTM student satisfaction's to saw response from the student toward the business sector. As the study was conduct in Bandar Tun Razak, Jengka, the researchers used primary resources by giving out a questionnaire to the student in order to get the information, seek and explore on the average of spending per student in a month, influential of the resident or non-resident student to the business sectors, the level of student satisfaction to the business sectors and the type business sector that give highest attraction to the students. The instruments that the researchers used were the questionnaire. This questionnaire design was applied to investigate the research questions. The instrument based from the topic, unit of analysis, research objectives and research question which the method to collect the data collection for this study. Overall, the business sector that attracts the UiTM student most was food. The researcher had contributed questionnaires to degree student at UiTM Pahang and overall most of the student answer food is the first business sector that they attracted most. To add, degree students at UiTM Pahang mostly not agree that they satisfied with the business sector in Bandar Tun Razak Jengka. The researcher's analysis indicated that the respondent that not satisfied were higher than the student who satisfied with the business sector in Bandar Tun Razak Jengka. The researchers also found that, there were no differences in total spending between resident and non-resident UiTM' s student. This occurs because they have the same basic needs, most of resident and non-resident student spending on the same thing such as food, cloth, stationery and etc. But in terms of ranking, there were different between resident and non-resident student. Overall, from the study, UiTM Pahang has stimulated the economy of Bandar Tun Razak Jengka. The existence of UiTM Pahang was not only boosted the local development environment but also the economic growth especially the residents income. Along the development of UiTM Pahang, the business sectors around UiTM Pahang also developed. As time move on, the business sector in Bandar Tun Razak Jengka was expanded as more UiTM student comes in. As the population of student increase, the demand also increase and it will give impact to the business sectors in Bandar Tun Razak, Jengka.